E-MODULE DESIGN FOR THE AUDIO VIDEO SYSTEM DESIGN COURSE BASED ON EPUB - satia fazria; Hari Anna Lastya (SciencePlus, 2026)
This research is motivated by the unavailability of EPUB-based e-modules in the Audio Video System Design course, so that more interesting, interactive, and easily accessible learning media are needed. The purpose of this research is to design and determine the feasibility of EPUB-based interactive e-modules as learning media. The method used is Research and Development (R&D) with the Borg & Gall model simplified to the product revision stage, through design planning with Canva, conversion to EPUB using Convert.io, and the addition of interactive features through Kotobee Author. The validation results show that the e-module obtained a feasibility percentage from media experts with an average score of 85%, and from material experts at 91%, all of which are in the very feasible category. Thus, the developed EPUB-based interactive e-module is declared valid, practical, and suitable for use as a learning medium in the Audio Video System Design course.